2018
DOI: 10.1016/j.nicl.2018.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Towards patient-specific modeling of brain tumor growth and formation of secondary nodes guided by DTI-MRI

Abstract: Previous studies to simulate brain tumor progression, often investigate either temporal changes in cancer cell density or the overall tissue-level growth of the tumor mass. Here, we developed a computational model to bridge these two approaches. The model incorporates the tumor biomechanical response at the tissue level and accounts for cellular events by modeling cancer cell proliferation, infiltration to surrounding tissues, and invasion to distant locations. Moreover, acquisition of high resolution human da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…Similar patterns of increased integration within the ipsilesional hemisphere have been reported in cerebral glioma cases, with one study finding increased functional integration of the hippocampus ( Esposito et al , 2012 ). However, from a structural connectivity standpoint, though consistent with previous findings of increased ipsilesional count, these results are inconsistent with the anatomical effects of glioma presence, which include tract displacement ( Schonberg et al , 2006 ; Angeli et al , 2018 ). With respect to the structural integrity of integration and modularity measures, we observed an ipsilesional decline.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Similar patterns of increased integration within the ipsilesional hemisphere have been reported in cerebral glioma cases, with one study finding increased functional integration of the hippocampus ( Esposito et al , 2012 ). However, from a structural connectivity standpoint, though consistent with previous findings of increased ipsilesional count, these results are inconsistent with the anatomical effects of glioma presence, which include tract displacement ( Schonberg et al , 2006 ; Angeli et al , 2018 ). With respect to the structural integrity of integration and modularity measures, we observed an ipsilesional decline.…”
Section: Discussionsupporting
confidence: 49%
“…One possible explanation attributes this to the cortical neuroplasticity described earlier, primarily the idea of recruitment of contralesional brain regions to aid its ipsilesional counterparts, a phenomenon noted in functional recovery of stroke patients ( Small et al , 2002 ). Another could be mass effect concentrating surrounding fibres, providing the fibre tracking algorithm to read an increase in connectivity between two lesion proximal nodes ( Schonberg et al , 2006 ; Angeli et al , 2018 ). Finally, the presence of oedema could be affecting fibre tracking, feigning the presence of increased connectivity while also showing an decrease in FA and increase mean diffusivity ( Field and Alexander, 2004 ; Wu et al , 2004 ; Bulakbaşı, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we did not directly measure tract displacement, since we did not use a normal control for comparison. However, previous studies have demonstrated that the degree of mechanical displacement of brain tissue caused by mass effect is reflected by a change in diffusion coefficients [65]. To control for the relative difference in sampled voxels between the two hemispheres and to assess whether tumor mass correlated with any of the measured diffusion coefficients, we compared the lesion volume, as a fraction of total intracranial volume, with the percent difference in diffusion coefficient between the hemispheres (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…DTI data have been used successfully in the context of glioma evaluation in several regards. For example, they have been used to adapt target volume definitions for GBM treatment planning [24][25][26], for modeling of brain tumor growth [27][28][29][30], to detect early malignant transformation of low-grade glioma [31], to differentiate between GBM and brain metastases [32], to use DTI-derived fiber tracking in surgery planning [33], and to detect the infiltration of the corpus callosum [34]. Our inability to properly connect most primary and secondary tumors does not diminish the value of DTI for these applications.…”
Section: Discussionmentioning
confidence: 99%